Media exposure and Chinese college students’ attitudes toward China’s maritime claims and disputes in the South and East China Seas - Hongyu Wang; Tianji Cai (Cogent Social Sciences, 2018)
China’s growing assertiveness in dealing with maritime territorial disputes has significant ramifications for regional peace and stability. Chinese government has been increasingly responsive to public opinion when making foreign policy. Media in China may play an important role in guiding public opinion and influencing the direction of China’ foreign policy. This study uses the survey method to compare the effect of differential media exposure on Chinese college students’ attitudes toward China’s maritime claims and disputes in the South and East China Seas. We find that intentional news exposure on China’s state media, commercial media, and online news outlets exerts no effect on Chinese college students’ attitudes toward China’s foreign policy. By contrast, incidental news exposure on WeChat (a relationship-oriented social media network) plays a larger role in increasing Chinese college students’ support for the forceful resolution of maritime disputes than Weibo (a news media site), when students communicate in a homogeneous environment. Moreover, cross-cutting exposure on Weibo is conducive to the development of moderate, reasoned, and open-minded opinions on China’s foreign relations, but students cannot reap the same benefits of cross-cutting exposure on WeChat. These findings support both the selective exposure hypothesis (intentional exposure) and the large media effect model (incidental exposure). We contribute to the literature by emphasizing the importance of differentiating media exposure mode, media content, and the relationship structure of social media when studying media effects on public opinion formation.